Atypical viral exanthems associated with community-acquired respiratory viruses in immunocompromised pediatric patients: a case series - Michelerio, Andrea; Svizzero, Alessandro; Brazzelli, Valeria (Frontiers in Medicine, 2025)
Atypical viral exanthems can pose significant diagnostic challenges in immunocompromised pediatric patients, where rashes may mimic drug reactions, infections, or graft-versus-host disease—conditions that require different and sometimes conflicting management strategies. These fragile patients, immunocompromised because of their underlying disease or treatment, require accurate and timely diagnosis to guide appropriate care. When the etiology is infectious, recognition also has public health and infection control implications. We describe four cases of atypical exanthems in children with oncohematologic diseases or solid tumors associated with community-acquired respiratory viruses-rhinovirus or respiratory syncytial virus (RSV)-confirmed by molecular diagnostics. The rashes were transient, nonpruritic or mildly pruritic, and predominantly involved the trunk and extremities. All rashes resolved spontaneously with no change in current therapy and no invasive procedures were required. These findings underscore the role of respiratory viruses such as rhinovirus and RSV in cutaneous manifestations and highlight the utility of noninvasive molecular testing to avoid misdiagnosis and overtreatment. Reports of such viral exanthems remain scarce in the literature. Our case series expands the clinical spectrum of rashes associated with rhinovirus and RSV and underscores the importance of a multidisciplinary approach to cutaneous manifestations in pediatric oncology patients.